Stable oxygen isotopes of the planktonic foraminifera Globigerinoides ruber and calculated d18O of seawater from 2.5 to 1 Ma - Jacek Raddatz; Christian Zeeden; Jorit Kniest; Dirk Nürnberg (PANGAEA, 2025)
Measured stable oxygen isotopes measured on a surface dwelling (G.ruber) and deep dwelling foraminifera (G truncatulinoides) from a sediment core in the tropical Pacific retrieved during research cruise SO-225 to the Manihiki Plateau. Oxygen isotopes ratios of this dataset have been combined with previously published temperature reconstruction using Mg/Ca ratios (Raddatz et al. 2017, Raddatz et al 2019) to calculate the d18O of seawater through time (2.5 to 1.0 Ma) of the sea surface and deep thermocline. We also provide a surface and deep thermocline d18O-seawater record that has been correct for global ice volume using the modelled ice sheet evolution through the Quaternary by Bintanja and Van de Wal (2008).
In: Raddatz, J et al. (2025): Stable oxygen isotopes of planktonic foraminifera of sediment core SO225-53-3, including calculated d18O of seawater (with and without ice volume correction) [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.984802